Human Aspects in Ambient Intelligence Contemporary Challenges and Solutions - Bosse, Tibor; Cook, Diane J.; Neerincx, Mark.; Sadri, Fariba; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2013)
This book presents recent developments is the field of human aspects in Ambient Intelligence. This field, and the associated workshop series, addresses multidisciplinary aspects of AmI with human-directed disciplines such as psychology, social science, neuroscience and biomedical sciences. The aim of the workshop series is to get researchers together from these human-directed disciplines or working on cross connections of AmI with these disciplines. The focus is on the use of knowledge from these disciplines in AmI applications, in order to support humans in their daily living in medical, psychological and social respects. The book plays important role to get modellers in the psychological, neurological, social or biomedical disciplines interested in AmI as a high-potential application area for their models. From the other side, the book may make researchers in Computer Science and Artificial and Ambient Intelligence more aware of the possibilities to incorporate more substantial knowledge from the psychological, neurological, social and biomedical disciplines in AmI architectures and applications.
A Clustering Approach to Intention Recognition -- Adaptive Autonomy in Unmanned Ground Vehicles Using Trust Models -- Automated Analysis of Non-Verbal Expressive Gesture -- Behaviometrics for Identifying Smart Home Residents -- SoundingARM - Assisted Representation of a Map -- Ambient Support by a Virtual Coach for Exercising and Rehabilitation -- Using Multiple Self Theory of Planner and Doer as a Virtual Coaching Framework for Changing Lifestyles: The role of Expert, Motivator and Mentor Coaches -- A Network of Sensor and Actuator Agents for Building Automation Systems -- From Mobile Cognition to Cognitive Mobility: QoS-Aware, Mobile Healthcare Services -- Mobile Phone Tools with Ambient Intelligence for the Management of Life-Threatening Allergies.
Keywords: Computer science; Medical records -- Data processing; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Computer Applications; Health Informatics; Simulation and Modeling